Aplikasi metode Material Requirement Planning (MRP) pada CV. Kana permadi dalam merencanakan kebutuhan bahan baku - Dwiyanti, Dessy (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The global pandemic of the Covid-19 virus has resulted in high demand for face masks as a means of personal protection against the transmission of the virus. Several Micro, Small, and Medium Enterprises (MSMEs) have started to produce their cloth masks because it is increasingly challenging to obtain surgical masks/medical masks. The planning of raw materials can determine the efficiency of production costs and profits from this business. Material Requirement Planning (MRP) is a system or concept used to manage raw material demand planning to meet the expected quantity of raw materials in production is called Material Requirement Planning (MRP). In this research, the author wants to help SMEs, especially CV. Kana Permadi is engaged in making cloth masks to manage the use of their raw materials optimally. They can reduce the cost of raw material inventory and obtain maximum profit by applying the MRP method. In addition, the authors want to know the effect of MRP on the planning of the raw material inventory of the cloth mask product. This study uses the MRP method with the EOQ technique to predict the number of raw material needs for the next period. Exponential Smoothing and Least Squares methods are used. The study results obtained the total cost of planning raw materials CV. Kana Permadi, with the conventional way from April 2020 to March 2021, is IDR 258,763,200 while using the MRP method with the EOQ technique, and the inventory cost is only IDR 46,827,179. So that the application of EOQ techniques on inventory management CV. Kana Permadi in producing cloth masks resulted in inventory cost savings of Rp.211,936,021. In addition, this study proves that the MRP technique can be used in various industries, including MSMEs engaged in convection, such as the production of cloth masks.